2018
DOI: 10.31689/rmm.2018.25.4.219
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia, as a Predictor Factor of Severe Acute Pancreatitis

Abstract: Dyslipidemia constitutes a well-known factor that can lead to acute pancreatitis. Hypertrigliceridemia and hypercholesterolemia are part of dyslipidemia. In a prospecitve study, we analyzed the role of hypercholesterolemia in triggering episodes of acute pancreatitis and the capacity of cholesterol blood level to predict the severity and the evolution of acute pancreatitis. In our prospective study, a preexistent cholesterol blood level above 240 mg/dl proved to be a trigger for pancreatitis and an increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Several studies also reported relationship between a high serum low-density lipoprotein cholesterol (LDL-C) level and severe acute pancreatitis. [24][25][26] One possible explanation is that oxidative stress resulting from chronic elevation of the serum LDL-C level plays an important role in pancreatic inflammation. 24,26 Thus, it may be possible that hyperlipidemia aggravates pancreatic inflammation induced by cannulation injury.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also reported relationship between a high serum low-density lipoprotein cholesterol (LDL-C) level and severe acute pancreatitis. [24][25][26] One possible explanation is that oxidative stress resulting from chronic elevation of the serum LDL-C level plays an important role in pancreatic inflammation. 24,26 Thus, it may be possible that hyperlipidemia aggravates pancreatic inflammation induced by cannulation injury.…”
Section: Discussionmentioning
confidence: 99%